Shark night [videorecording (DVD)] - Milligan, Dustin; Paxton, Sara; McPhee, Katharine, 1984-; Carmack, Chris, 1980-; Logue, Donal, 1966-; Leonard, Joshua; Moore, Joel David, 1977-; Fleiss, Mike, 1964-; Howell, Lynette, 1979-; Briggs, Chris; Hayes, Will; Studenberg, Jesse; et al. (20th Century Fox Home Entertainment, 2011)
When Sara and her friends arrive at her family's Louisiana lake house, they quickly strip down to their swimsuits for a weekend of sexy fun in the sun. But they soon discover the lake is infested with hundreds of flesh-eating sharks, and a few equally dangerous human predators, that turn their killer vacation into a bone-crunching battle to stay alive!